Application of four sets of tectonomagmatic discriminant function based diagrams to basic rocks from northwest Mexico - Pandarinath, K.; Verma, S. K. (Journal of Iberian Geology, 2013)
Abstract Discrimination diagrams are being widely used for the past four decades to infer the tectonomagmatic affiliation of old rocks. There are several major- and trace-element composition based bivariate, ternary and multi-element discriminant function diagrams in the literature. Recent evaluation of the performance of these diagrams indicates that four sets of recent discriminant function based diagrams, in which the tectonic boundaries are determined from probability estimates for four tectonic settings of island arc, continental rift, ocean-island and mid-ocean ridge, have shown very high success rates. In this work, we have created an extensive geochemical database for on-land and off-shore basic rocks of northwest Mexico and applied these four sets of recent and highly successful tectonomagmatic discriminant function based diagrams to infer their tectonomagmatic origin. Each of these four sets of diagrams (two for major- and two for trace-elements) contained five diagrams. All the four sets of diagrams confirmed a continental rift setting for on-land basic rocks of <13 Ma age, with success rates of 71%-93% and 58%-90% for major-element and traceelement based diagrams, respectively. For the on-land basic rocks of >13 Ma age, major-element based diagrams also indicated a rift setting. However, one set of trace-element based discrimination diagrams indicated an arc to rift transition and the other set of trace- element based discrimination diagrams for the only sample from the Comondú arc, which has the required complete dataset, indicated an arc setting. All the four sets of discrimination diagrams indicated MORB setting (success rates 90%-98% and 100% for major-element and trace-element based diagrams, respectively) for off-shore rocks (most of the samples were obtained from DSDP drilled sites in the Gulf of California and some dredged rock samples from the Gulf of California) with very high success rates. All the inferred tectonic settings from these four sets of new discrimination diagrams, in general, are in conformity with those reported in the literature based on other methods. The results show that these discrimination diagrams may successfully discriminate the original tectonic setting of comparatively younger and older on-shore rocks as well as sea-water altered deep-sea rocks and dredged material.